109k views
5 votes
Find the general solution of the differential equation y^(5) −2y^(4) + y^(3) = 0.

User Mmarion
by
6.1k points

1 Answer

3 votes


y^((5))-2y^((4))+y^((3))=0

We can reduce the order of the ODE by substituting
v(x)=y^((3))(x), so that
v'(x)=y^((4))(x) and
v''(x)=y^((5))(x). Then


v''-2v'+v=0

has characteristic equation


r^2-2r+1=(r-1)^2=0

with root
r=1, which has multiplicity 2, so that the characteristic solution is


v_c=C_1e^x+C_2xe^x

Integrate both sides to solve for
y''(x):


y''=C_1e^x+C_2e^x(x-1)+C_3


y''=C_1e^x+C_2xe^x+C_3

Integrate again to solve for
y'(x):


y'=C_1e^x+C_2e^x(x-1)+C_3x+C_4


y'=C_1e^x+C_2xe^x+C_3x+C_4

And one last time to solve for
y(x):


y=C_1e^x+C_2e^x(x-1)+\frac{C_3}2x^2+C_4x+C_5


\boxed{y(x)=C_1e^x+C_2e^x+C_3x^2+C_4x+C_5}

User Desfido
by
5.3k points